Mechanism of Hbγ-35-induced an increase in the activation of the human immune system by endotoxins. Issue 3 (April 2015) - Heinbockel, Lena; Palacios-Chaves, Leyre; Alexander, Christian; Rietschel, Ernst; Behrends, Jochen; Correa, Wilmar; Fukuoka, Satoshi; Gutsmann, Thomas; Ulmer, Artur J; Brandenburg, Klaus
Endotoxins (LPS) are highly potent immune stimulatory molecules and are mainly known for triggering Gram-negative sepsis. However, besides their toxic effects, this stimulatory function may be advantageous, for example when used as an adjuvant during vaccination. Thus, there is always a narrow range between the useful wake-up of the immune system and its overwhelming reaction, which can lead to diseases like sepsis. This raises the question of which conformational properties are responsible for making the LPS aggregates more or less potent. As described previously, the size, type and form of LPS aggregates play a major role in their immune stimulatory activity. In this study we investigate the role of these parameters. On the one hand, we use a peptide (Pep19-2.5; Aspidasept) that causes a change of the LPS aggregate structure into a less toxic state; on the other hand, we use a potent immune stimulating peptide (Hbγ-35), leading to higher toxicity. We have found opposing effects on LPS aggregate conformations allowing a better understanding of the processes of immune stimulation.